2018
DOI: 10.1002/hrm.21943
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing meaningfulness climate in teams: How spiritual leadership enhances team effectiveness when facing uncertain tasks

Abstract: This study integrates social information processing theory with leadership and climate literature, and aims to produce novel theoretical insights into whether and how spiritual leadership and task uncertainty foster conditions to enhance meaningfulness climate and subsequent team effectiveness in China. Team effectiveness was operationalized as team performance and team organizational citizenship behavior (OCB). Based on data collected at three time points over 12 months from multiple sources of 123 teams in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 100 publications
(173 reference statements)
4
57
0
7
Order By: Relevance
“…Organizational learning [81] Organizational citizenship behavior [59] Higher productivity, performance excellence [31,78,84] Greater flexibility of the organization [84] Greater creativity of the organization [84] Faster growth, higher efficiency [81] Some findings have indicated that spirituality influences learning in teams, spiritual climate, and team-level innovative behaviors [83]. The more humane a workplace is, the more productive, flexible, and creative the organization is [84]. This can cause an increase in high-performing teams [78].…”
Section: Individual Levelmentioning
confidence: 99%
“…Organizational learning [81] Organizational citizenship behavior [59] Higher productivity, performance excellence [31,78,84] Greater flexibility of the organization [84] Greater creativity of the organization [84] Faster growth, higher efficiency [81] Some findings have indicated that spirituality influences learning in teams, spiritual climate, and team-level innovative behaviors [83]. The more humane a workplace is, the more productive, flexible, and creative the organization is [84]. This can cause an increase in high-performing teams [78].…”
Section: Individual Levelmentioning
confidence: 99%
“…Thus, the independence of the BoD is enough to promote "CE policies related to communication with employees." We contribute to social information processing theory for employees (Yang et al, 2019) empirically showing a determinant of the possibility to process work and social information, that is, the development of the possibilities for employees to understand their work situations and process social information is promoted by a high independent BoD.…”
Section: Regression Resultsmentioning
confidence: 99%
“…The presence of many independent directors aims to guarantee a definition of a CE suitable for employee because principles and rules can represent employees' interest and needs, like the need of communication. Thus, the independence of the BoD is enough to promote “CE policies related to communication with employees.” We contribute to social information processing theory for employees (Yang et al, 2019) empirically showing a determinant of the possibility to process work and social information, that is, the development of the possibilities for employees to understand their work situations and process social information is promoted by a high independent BoD. Given that, CE has an impact on work climate and workplace health and safety (Manley, 1991; O'Dwyer & Madden, 2006; Williams & Murphy, 1990), a large component of independent directors, indirectly promoting polices in CE, can improve the work environment in these terms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations